Improving Interactive Multimedia Based Learning Media for Elementary School Students - Erni Pradita; Zakiya Ramadhina Azhar; Wahyu Kurniawati (Educare: Journal Educational and Multimedia, 2024)
This study aims to develop interactive multimedia-based learning media for solar system material for grade VI elementary school students that is feasible in terms of validity, practicality, and effectiveness. The method used in research is research and development or Research and Development using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research data collection instruments were media expert validation sheets, material expert validation sheets, teacher questionnaire sheets, student questionnaire sheets, pretest and posttest. The data analysis technique used in this study is the validity test, the practicality test and the effectiveness test of learning media. The results of the learning media validity data were obtained based on the results of the media validation assessment by experts who obtained a percentage of 96.67% in the "very valid" category and the results of the material validation assessment by experts who obtained a percentage of 95 % in the "very valid" category. The results of the practicality of learning media data were obtained based on the results of the teacher's questionnaire assessment which obtained a percentage of 93.75% in the "very practical" category and the results of the student questionnaire assessment which obtained a percentage of 94.63% in the "very practical" category. The results of the data on the effectiveness of learning media were obtained from student learning outcomes on the pretest - posttest scores. That way, it is known that there is a significant increase in the N-Gain analysis with an average acquisition of 0.74 in the high category and a learning completeness percentage of 100% in the "very good" category. So it can be concluded that learning media based on interactive multimedia on solar system materials is feasible to be used as a learning medium.